Research progress on the mechanism by which skin macrophage dysfunction mediates chronic inflammatory injury in diabetic skin - Huang, Jiali; Zhang, Shili; Ding, Xinyi; Li, Shuxian; Luo, Xiangrong; Cao, Ying; Gao, Fang; Zou, Mengchen (Frontiers in Endocrinology, 2022)
Macrophages, the main immune cells in the skin, form an innate immune barrier. Under physiological conditions, skin maintains immune barrier function through macrophage phagocytosis and antigen presentation. Parenchymal and stromal cell regeneration plays an important role in skin injury repair and uses macrophage plasticity to influence and stabilize the skin microenvironment. Diabetic skin lesions are the most common diabetes complication and are involved in the early pathophysiology of diabetic foot. Therefore, studying the initial link in diabetic skin lesions is a research hot spot in the early pathogenesis of diabetic foot. Skin inflammation caused by hyperglycaemia, oxidative stress and other injuries is an important feature, but the specific mechanism is unknown. Recent studies have suggested that chronic inflammatory injury is widely involved in a variety of skin diseases, and whether it plays an important role in diabetic skin lesions is unclear. In this review, current research hotspots were combined with the pathogenesis of diabetic skin lesions and analysed from the perspectives of the physiological function of skin macrophages, the impairment of skin macrophages in diabetes, and the mechanism of chronic inflammatory injury in macrophages to provide a theoretical basis for early screening and evaluation of diabetic foot.